Perancangan Interior Galeri Supercar Amerika di Surabaya - Grace Mulyono, Ivan Farandy M. Solahuddin (Intra, 2013)
American car Supercar timeless design is said to be due to changes in each generation American Supercar car, definitely will not change drastically from its predecessor and is also known as muscle car because the average American has a super car that had a big cc engine, the paradigm that considers expensive American car products, exclusive and rare, so people are reluctant to visit the showroom, therefore American supercar design gallery in Surabaya is intended to invite the public to know the ins and outs, advantages and quality of American super car. Designing interior design purposes the American supercar Gallery In Surabaya convenient and informative style that has a modern hitech facilities hangout, cafes, spare parts and repair shop. Hi tech style, used for vehicle types Supercar loaded with technology and to highlight facilitate the delivery of information technology. Cozy atmosphere in this design is achieved through the complete facilities and atmosphere of the interior. Because Supercar America is not like a regular car, the use of materials and new materials. Informative atmosphere is achieved through the use of LED display panel and display that shows information bias. Application of shine in the dark theme applied to colors, materials and formations such as the use of finishing an impressive shine and gloss black or dark colors to impress dark.